2008
DOI: 10.1016/j.neuron.2008.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Precise Circuitry Links Bilaterally Symmetric Olfactory Maps

Abstract: Olfactory sensory neurons expressing a common receptor gene converge onto one or a few glomeruli with stereotyped positions within the mouse main olfactory bulb (MOB), producing a map of approximately 1800 olfactory columns representing approximately 1000 odorant receptors. Here, we report that this precise olfactory map is maintained over several synapses that ultimately cross MOB hemispheres to link bilateral isofunctional olfactory columns. Focal injection of tracer into genetically identified glomeruli rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
135
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(146 citation statements)
references
References 43 publications
(60 reference statements)
8
135
1
2
Order By: Relevance
“…AONpE receives topographical axonal projections from the ipsilateral OB (11,(16)(17)(18), raising the possibility that the odorant category tuning of ipsinostril input to individual AONpE neurons is a result of the topography of afferent projection from the ipsilateral OB. In accordance with this hypothesis, Johnson et al demonstrated that sulfide-category odorants activate glomeruli at the ventro-caudal region in the ventral zone of the OB (19), and mitral/tufted cells in these regions project axons to the ventrocaudal region of the AONpE (11,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AONpE receives topographical axonal projections from the ipsilateral OB (11,(16)(17)(18), raising the possibility that the odorant category tuning of ipsinostril input to individual AONpE neurons is a result of the topography of afferent projection from the ipsilateral OB. In accordance with this hypothesis, Johnson et al demonstrated that sulfide-category odorants activate glomeruli at the ventro-caudal region in the ventral zone of the OB (19), and mitral/tufted cells in these regions project axons to the ventrocaudal region of the AONpE (11,18).…”
Section: Discussionmentioning
confidence: 99%
“…In one candidate pathway (Fig. 5A), contralateral AONpE neurons send topographically organized commissural projections to the ipsilateral OB (17,18,20,21) and form excitatory synaptic inputs on granule cells ("G" in Fig. 5A) that inhibit mitral and tufted cells (22).…”
Section: Discussionmentioning
confidence: 99%
“…Both the distribution and somato-dendritic characteristics of MNs differ from those of neurons in the deep layers of the MOB (Blanes 1898; Ramón y Cajal 1904; Macrides and Davis 1983; Scott et al 1987;López-Mascaraque et al 1986;Eyre et al 2008) or AOB (Larriva-Sahd 2008). An MN possesses a dendritic field strategically distributed to maximize inputs from the ipsilateral and commissural efferent axons arising from either side of the anterior olfactory nuclei (Valverde 1965;Price 1974;Schoenfeld and Macrides 1984;Reyher et al 1988;Yan et al 2008). The axon from both subtypes of MNs (i.e., spiny and aspiny) passes among the cellular clusters of the RMS that diverge toward the olfactory cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Lead and uranium staining, adult rat brain. Bars 1 μm (a), 0.3 μm (b, c) 2006; Valverde 1965;Reyher et al 1988;Yan et al 2008). Because AON efferent fibers travel in the bulbar white matter, which sends collaterals to MNs, MNs are probably controlled by olfactory activity.…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced membrane excitability and recurrent synaptic excitation within the AON, together with its widespread outputs, suggest that the AON can boost and distribute activity in feedforward and feedback circuits throughout the olfactory system. piriform cortex; preendopiriform nucleus; area tempestas; afterhyperpolarization; inward rectifying potassium channels; cable properties; pyramidal neuron WITH ITS FEEDBACK CONNECTIONS to the ipsilateral and contralateral olfactory bulbs, and feedforward connections to the piriform cortex, the anterior olfactory nucleus (AON) is poised to coordinate the flow of activity between olfactory areas (Alheid et al 1984;Reyher et al 1988; Haberly and Price 1978;Yan et al 2008). The entire AON receives input from the ipsilateral olfactory bulb, but it is divided into subregions by the topography of output projections and cytoarchitecture ( Principal neurons in pars principalis of AON are particularly well positioned to influence activity in piriform cortex for several reasons.…”
mentioning
confidence: 99%